2022
DOI: 10.1002/deo2.103
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of duckbill‐type anti‐reflux self‐expandable metal stents for distal malignant biliary obstruction with duodenal invasion: A pilot study

Abstract: Objectives Early obstruction of a self‐expandable metal stent placed for distal malignant biliary obstruction is more likely to occur in the presence of duodenal invasion. An anti‐reflux self‐expandable metal stent (ARMS) has been developed for the purpose of preventing duodenal fluid reflux into the bile duct. In this study, we evaluated the usefulness and safety of a duckbill‐type ARMS (D‐ARMS) in the situation of duodenal invasion. Methods We retrospectively analyzed 10 consecutive patients who received D‐A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Since a previous in vitro study showed that a duodenal pH environment caused a morphological change of ARV, 27 the development of a new ARV that is not affected by the duodenal pH environment might be necessary to improve the durability of the ARV. Third, the rate of tumor ingrowth was high in this study (18%) compared to previous studies using DMS 12,13,15,28 . This could be explained by the difference in the proportion of SEMS‐naïve patients and the duration of the indwelling period of SEMS 29 .…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Since a previous in vitro study showed that a duodenal pH environment caused a morphological change of ARV, 27 the development of a new ARV that is not affected by the duodenal pH environment might be necessary to improve the durability of the ARV. Third, the rate of tumor ingrowth was high in this study (18%) compared to previous studies using DMS 12,13,15,28 . This could be explained by the difference in the proportion of SEMS‐naïve patients and the duration of the indwelling period of SEMS 29 .…”
Section: Discussionmentioning
confidence: 52%
“…Third, the rate of tumor ingrowth was high in this study (18%) compared to previous studies using DMS. 12 , 13 , 15 , 28 This could be explained by the difference in the proportion of SEMS‐naïve patients and the duration of the indwelling period of SEMS. 29 We speculated that the external force applied to the covered membrane of a laser‐cut type SEMS may become strong enough to cause tumor ingrowth, especially when used in SEMS‐naïve patients with a long indwelling time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation